Green-Fuel Production Through Co-Processing Biomass Derived Oil with Standard Gasoil Feedstock - Rizki Ekananda; Rokhmaturrokhman Rokhmaturrokhman; Wilda Yuni Parinduri; Zaky Al Fatony (ALCHEMY Jurnal Penelitian Kimia, 2025)
To enhance refinery revenue through the use of new and renewable materials, lab-scale research on green-fuel production has been conducted. This involved co-processing biomass-derived oil with standard gasoil feedstock and existing E-cat to assess its feasibility for commercial fluidized catalytic cracking (FCC) units. The catalytic cracking process varied the type of biomass-derived oil (Crude Palm Oil (CPO) and Refined Bleached Deodorized Palm Oil (RBDPO)) against standard gasoil, using typical operating parameters: cracking temperature of 510 °C, C/O ratio of ~6, and regenerator temperature of 715 °C. The Advanced Cracking Evaluation (ACE) reactor modeled one cycle of reaction and regeneration. Product yields were calculated using mass balance of liquid and gas products, modeled with GC Simdist, GC RGA, and CO2 Analyzer, while gasoline octane number was based on PONA composition using GC DHA. Results showed conversion rates of 85-86%, Research Octane Number (RON) of 91.2 – 93.55, and product yields for coke, dry gas, propylene, LPG, gasoline, LCO, and bottom fraction in the ranges of 6.9 – 7.1%, 1.26 – 3%, 6.79 – 8.5%, 19.52 – 23.1%, 44.8 – 51.63%, 10.21 – 11.4%, and 3 – 3.68%, respectively. Both CPO and RBDPO can be used as co-processing feedstock in FCC units, but adjustments in operating conditions, catalyst formulation, or optimization of the wet gas compressor may be needed due to higher light fraction (Propylene and LPG) and lower gasoline production.